Prevention and Safety Training to Improve Community Health - Vajihe, Keshaverz (International Journal of Occupational and Environmental Medicine, 2023)
Background and Purpose Public health problems are caused by the emergence of environmental pollution and infectious diseases, which have caused concern around the world. The public health threat affects the relationship between people. Population growth and associated pressures increase difficulties associated with effective means of maintaining public health. The diseases transmitted from human and livestock communication, water pollution, air pollution, and environmental pollutants urge us to find new solutions to address these problems. Understanding the environmental and environmental health is a prerequisite for protecting public health. In Iran, like other countries in the world, the issue of environmental protection and its compliance with the first program of economic, social and cultural development of the Islamic Republic has begun and expanded in the future. In this regard, new perspectives are being introduced that will bring about dramatic changes at various levels of planning, processes and specialized sectors such as civil, industrial and educational sectors. The training of engineers in this regard can play a very important role in refining the attitudes of young engineers and using these bases in their specialized activities. One of the important tasks of universities is to provide a suitable platform for such training. In this regard, it is essential that the major industrial universities of the country develop various programs in this field. Materials and Methods The present study is a review of the type of validity that is performed through search of authoritative scientific databases such as PubMed and Scopus, Google scholar, PubMed using the key words of building safety and health, HSE, and prevention methods are the latest information. Results Implementing the principles of HSE in various construction, industrial and other projects requires time, because any change that is considered in the system requires a change of attitude, which in turn requires time to adapt and adapt to the new conditions. The conditions for the projects in this research are their current conditions, and the next research, after a while, can determine the percentage of project progress in terms of HSE. Conclusion In order to comply with the principle of HSE cases, there is a need for training. These trainings should be executed at different levels and levels of contracting and monitoring so that the level of awareness of the risks involved in the development of civil operations between the personnel reaches a common frontier.
Keywords: Prevention and Health; HSE; Occupational Health Engineering; Health Management